Anther and internode culture of kenaf (hibiscus cannabinus) - Muhammad Akram Mohd Noordin (2014)
This study is about induction of callus from anther and internode of Hibiscus cannabinus. The objectives of this study are to investigate the effect of different combination and/or concentration of hormones on the callus induction from anther and stem culture. Anthers of kenaf from selected flower bud are sterilized following Khatun, (2003). For internode culture, four trials had been performed by using different sterilization techniques and types of internode used following Mclean et al., (1992). Both anther and stem were cultured in MS media supplemented with different combination/ concentration of hormones (BAP and NAA). The results showed that anthers cultured on the MS media supplemented with 1.0 mg/I NAA + 3.0 mg/I BAP and 2.0 mg/I NAA + 3.0 mg/I BAP gave the highest number of callus induction with the percentage of 100%. However, callus induction in media supplemented with 1.0 mg/I NAA + 3.0 mg/I BAP shows growth of roots after 4 weeks of culture. For internode culture, the fourth trial gave the best outcome where MS media supplemented with 1.0 mg/I NAA + 3.0 mg/I BAP, 1.0 mg/1 NAA + 6.0 mg/I BAP and 2.0 mg/I NAA gives the highest percentage of callus induction.